Information-seeking in the Wake of Tragedy: An Examination of Public Response to Mass Shootings Using Google Search Data. (February 2022) - Semenza, Daniel Charles; Bernau, John A.
Mass shootings are a highly visible form of violence in the United States, although public response to these events varies considerably. Drawing on social problems and collective threat perception literature, we use search data for all Google-using Americans following mass shootings since 2004 to examine how event attributes such as the number of victims, venue, and type of weapon(s) predict public information-seeking related to gun control and gun rights. The results demonstrate that the number of victims, news coverage, school venue, and the use of certain weapons all significantly increase public interest in gun control and gun rights. These key predictors interact with one another to further influence information-seeking behaviors related to both gun control and gun rights. We conclude with a discussion of our findings and the potential for Google Search data in social science research.